Doppler shift determination methods dedicated to MBFSK modulation - Czapiewska, Agnieszka; Łuksza, Andrzej; Schmidt, Jan H.; Studański, Ryszard; Wojewódka, Łukasz; Żak, Andrzej (Zielona Góra: Uniwersytet Zielonogórski)
The progressive development of AUVs (Autonomous Underwater Vehicles) is creating demand for wireless underwater communications. The most commonly used transmission medium in water is acoustic wave. Unfortunately, the underwater hydroacoustic channel is characterized by strong multipath, especially in shallow reservoirs and in combination with hydrotechnical infrastructure. In addition, there is a Doppler effect in the case of reciprocal movement of the transmitting and receiving parts.
Keywords: underwater communication; multipath channels; Doppler shift; Doppler measurement; MBFSK